ANALISIS LITERASI KEUANGAN MAHASISWA S-1 FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO ANGKATAN 2014 - 2017 - Sakinah, Gina; Mudakir, Bagio (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
Financial management failure occurs when students do not have good financial literacy. Students must have good knowledge, attitude, and behavior in managing their personal finances. This study aims to analyze the level of financial literacy of undergraduate students of the Faculty of Economics and Business at Diponegoro University class of 2014 to 2017 and the factors that influence it. Financial literacy in this study uses a financial literacy index consisting of components of the knowledge, attitude, and financial behavior of students. The research data uses primary data with questionnaires and sample of 100 students. Meanwhile, the method used in this study is descriptive statistics and multiple linear regression test (OLS). As a result, the level of student financial literacy is categorized as quite literary, that is 50.4%, influenced by age, GPA, parental education, and length of study. On the other hand, gender and income do not affect student financial literacy.